The Influence of Intelectual Intelligence and Spiritual Intelligence on Non-Manager Employees Performance at Amaris Hotel on Tasikmalaya City (A Case Study on Non-Manager Employees at Amaris Hotel on Tasikmalaya City) - Dikri Mohamad Anzani; Suci Putri Lestari; Arga Sutrisna (Journal of Indonesian Management, 2022)
This purpose of this study to determine the effect of intellectual intelligence and spiritual intelligence on non-manager employees performance at Amaris Hotel on Tasikmalaya City (Case Study on non-manager employees at Amaris Hotel on Tasikmalaya City). The method used is a quantitative method with a research sample of 32 respondents who are a non-manager employee at Amaris Hotel on Tasikmalaya City. The data is used primary data and secondary data. The analitytical tool in this research is multiple regression using by SPSS version 25. The result showed that simultaneously intellectual intelligence and spiritual intelligence has a significant influence on employee performance. Partially intellectual intelligence has an unsignificant influence on employee performance. Partially spiritual intelligence has a significant on employee performance.